The Effect Of Work Discipline And Job Training On Employee Work Performance With Job Satisfaction As An Intervening Variable (Study Of The Prokopim Section Of The Jember Regency Secretariat) - Yuyun Istifarida; Budi Santoso; Riyanto Setiawan Suharsono (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to examine the influence of work discipline and job training on the work performance of employees of the Prokopim Section of the Jember Regency Secretariat with job satisfaction as an intervening variable. The problem raised is the extent to which discipline and job training can improve work performance directly or indirectly through employee job satisfaction. The research method used was quantitative with data collection through questionnaires and data analysis using path regression to test variable relationships. The results of the study show that work discipline and job training each have a positive and significant effect on work performance. In addition, both also have a significant effect on job satisfaction, which in turn becomes a mediating variable in strengthening the influence of these two variables on work performance. In other words, job satisfaction strengthens the positive impact of discipline and training on improving the work performance of Prokopim employees. The conclusion of the study emphasizes the importance of developing work discipline and continuous training, accompanied by efforts to increase job satisfaction as the main strategy in optimizing employee achievement. The implications of this research encourage Prokopim management to focus on improving the quality of training and the implementation of effective work discipline to create productive and motivated employees.